1987
DOI: 10.1152/ajprenal.1987.252.1.f60
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insulin on renal potassium metabolism

Abstract: The effect of insulin on renal potassium excretion was examined by employing the euglycemic insulin clamp technique in combination with renal clearance measurements. While euglycemia was maintained, insulin was infused at rates of 4.8 (n = 7) and 12 (n = 5) mU X kg-1 X min-1. Steady-state plasma insulin levels of 164 +/- 8 and 370 +/- 15 microU/ml were achieved in the low- and high-dose studies, respectively. Base-line plasma potassium concentration declined progressively by a mean of 0.14 +/- 0.09 (P less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…Acute experiments have suggested that insulin may cause hypokalemia by increasing potassium uptake in extrarenal tissues. 30 In the present study, plasma potassium concentration was slightly reduced during long-term insulin infusion. Another possible cause of the decrease in potassium excretion is an increase in sodium reabsorption before the distal nephron, which would tend to reduce distal nephron flow rate and potassium secretion.…”
Section: Hyperinsulinemia and Renal Excretionsupporting
confidence: 49%
“…Acute experiments have suggested that insulin may cause hypokalemia by increasing potassium uptake in extrarenal tissues. 30 In the present study, plasma potassium concentration was slightly reduced during long-term insulin infusion. Another possible cause of the decrease in potassium excretion is an increase in sodium reabsorption before the distal nephron, which would tend to reduce distal nephron flow rate and potassium secretion.…”
Section: Hyperinsulinemia and Renal Excretionsupporting
confidence: 49%
“…8 d after catheter insertion, rats in groups I-IV received a two-step euglycemic insulin-clamp study (20,21). Four rats in group III received a repeat two-step insulin-clamp study 14 was initiated and continued throughout the study (20).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the effects of insulin are very dependent on plasma glucose and K ϩ levels and often do not lead to salt retention and elevation in blood pressure (5,20). Furthermore, IGF-1 reduces renal potassium excretion (6), whereas insulin can promote kaliuresis (5), particularly when plasma K ϩ levels are exogenously clamped (9,36). The molecular details of the distinct effects of insulin and IGF-1 on urinary excretion patterns are not clear.…”
mentioning
confidence: 99%